A new design of photonic transmitter for terahertz spectroscopy and imaging applications - Ibtissame Moumane; Jamal Zbitou; M. Latrach; A. Errkik; O. Chakkor (IAES Indonesian Section, 2019)
In this paper we present the Design of Continuous Wave Terahertz photonic transmitter based on photodetector, THz antenna, and low-pass filter (LPF) and Direct Current “DC” Probe Bias. Before validating the whole system, we processed firstly with the optimization of the antenna which is responsible of the transmitting the RF signal providing from the photodetector then we have conducted a study on the design of a low pass filter “LPF” whose role is to block the received RF signal to reach the DC probe. After the optimisation of the proposed LPF, we have integrated the different components mounted on multi-layers GaAs substrate and simulated the final photonic transmitter by using an EM solver “Momentum” integrated in ADS “Advanced Design System”. The dimensions of the whole circuit are .The simulation results permit to validate the final circuit at 1.6 THz, the proposed photonic transmitter is suitable for terahertz spectroscopy and imaging applications.